How children succeed : grit, curiosity, and the hidden power of character - Tough, Paul (Boston : Houghton Mifflin Harcourt, 2012)
In this book the author reverses three decades of thinking about what creates successful children, solving the mysteries of why some succeed and others fail, and of how to move individual children toward their full potential for success. The story we usually tell about childhood and success is the one about intelligence: success comes to those who score highest on tests, from preschool admissions to SATs. But in this book the author argues that the qualities that matter most have more to do with character: skills like perserverance, curiosity, conscientiousness, optimism, and self-control. He uncovers the surprising ways in which parents do, and do not, prepare their children for adulthood. And he provides us with new insights into how to help children growing up in poverty. Early adversity, scientists have come to understand, can not only affect the conditions of children's lives, it can alter the physical development of their brains as well. But now educators and doctors around the country are using that knowledge to develop innovative interventions that allow children to overcome the constraints of poverty. And with the help of these new strategies, children who grow up in the most painful circumstances can go on to achieve amazing things. This book has the potential to change how we raise our children, how we run our schools, how we construct our social safety net, and also how to change our understanding of childhood itself.
How to fail (and how not to) -- How to build character -- How to think -- How to succeed -- A better path.
LC copy 1 signed by author.
Includes bibliographical references (pages 203-222) and index.
Keywords: Early childhood education -- United States; Cognitive styles in children -- United States; Cognitive styles in children; Early childhood education; United States; Kleinkinderziehung; Denkstil; Armut; Zufriedenheit; Erfolg; Erziehung; USA